Influence of racket length on tennis stroke - Kneib, B.; Schlarb, H.; Glitsch, U. (1998)
The current design of tennis rackets tends toward so-called long body rackets, expected to produce a higher rebound velocity because of the more distally situated hitting point. To study the influence of racket length on the tennis stroke, a standardized computer- model was used, as described by Detlefs and Glitsch (1996). This computer simulation allows a 100% reproducibility with an almost arbitrary time resolution and an independent variation of all input parameters. The experimentally determined geometrical mass distributions of several existing rackets served as input variables for this model. The interesting results are the rebound velocity of the ball and the joint forces of the grip, wrist and elbow. The investigation indicates that the shape of the longer rackets is either obtained by a simple elongation of the grip, keeping the design of the short version, or by creating a completely new design in regard to the mass geometry. As we can see from Fig 1, the gain from a 2% higher rebound velocity increases the loads in the wrist (16%), elbow (17%) and particularly the grip joint (212%), which results in no advantages at acceptable costs for the hobby player. On the other hand, more sophisticatedly designed long body rackets increase ball velocity without producing higher impact loads on the arm. Thus only rackets that are especially designed for a long version yield advantages in tennis performance. An increase in length alone is not a significant feature for the performance of a racket. References: Detlefs, C.; Glitsch, U. (1996). Kinetics of the computer simulated tennis stroke with different rackets. Proc. XIVth Intern. Symposium on Biomechanics in Sports, Funchal, 573-576.